The role of relatives’ expressed emotion and personality traits in predicting schizophrenia relapse - Roseliza-Murni AbRahman,; Fatimah Yusooff,; Asmawati Desa, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
The debilitating nature of schizophrenia and recurrent relapse of its psychotic episodes are often poorly understood and can be confusing to many family members, who play the role as primary caregivers. This study aimed at investigating the role of relatives’ expressed emotion (EE) and personality traits in predicting relapse among schizophrenia patients. A total of 160 subjects in which the dyads of 80 patients diagnosed with schizophrenia and 80 key relatives were recruited to participate in Phase 1 and then followed-up 6 months later for Phase 2 of the study. The Family Questionnaire (FQ) was administered to measure relatives’ EE level while Eysenck Personality Questionnaire-Revised (EPQ-RS) was used to measure their personality traits. Patients’ were considered to relapse if they were readmitted into the psychiatric wards within 6 months post-hospital discharge from their index hospitalization. Results showed that the odds for patients to relapse was increased by 8 folds when relatives demonstrated high-EE level. Relatives’ critical comments (CC) component turned out to be a strong predictor with 12% chance for schizophrenia relapse when they demonstrated an increase in CC level. Relatives’ personality traits particularly the lie scale and extraversion trait also turned out to be the significant direct predictors to patients’ relapse. Relatives with elevated lie scale score or also considered as the conformists predicted patients’ relapse almost 3 folds. On the contrary, a unit decreased in extraversion trait predicted the odds for patients to relapse by 29%. Results supported the worldwide findings on the significant role of relatives’ high-EE level particularly the CC component in predicting the course of schizophrenia. The significant contribution of relatives’ extraversion and conformism traits is indeed a novel finding in studies of schizophrenia relapse. Results generally supported the viability of EE construct in predicting relapse among local schizophrenia patients.